STRATEGI PENGUATAN KARAKTER PESERTA DIDIK DI SMPN 1 KARAWANG TIMUR DALAM PERSPEKTIFPENDIDIKAN GLOBAL - Mutia Sari, Tika; Eki Waluyo, Kasja; Aziz, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the strategies implemented by SMPN 1 Karawang Timur to strengthen students’ character within the framework of global education. In the era of globalization that demands 21st-century competencies, schools must instill essential character values such as integrity, discipline, cooperation, responsibility, and critical thinking skills. This research employs a qualitative descriptive method with data collected through observation, interviews, and documentation. The findings reveal that character strengthening is carried out through the integration of character values into the learning process, the development of a positive school culture, the optimization of extracurricular activities, and the enhancement of global literacy through collaborative programs and responsible digital practices. These strategies are considered effective in shaping students who are strong in character, adaptable, and globally minded while still upholding local cultural values. The results of this study are expected to provide guidance for other schools in developing character education strategies amidst global challenges.